PAMAM dendrimers as promising nanocarriers for RNAi therapeutics. Issue 10 (December 2015) - Kesharwani, Prashant; Banerjee, Sanjeev; Gupta, Umesh; Mohd Amin, Mohd Cairul Iqbal; Padhye, Subhash; Sarkar, Fazlul H.; Iyer, Arun K.
Abstract : Therapeutics based on RNA interference mechanisms are highly promising for the management of several diseases including multi-drug resistant cancers. However, effective delivery of siRNAs and oligonucleotides still remains challenging. In this regard, hyper-branched, PAMAM dendrimers having unique three-dimensional architecture and nanoscale size, with cationic surface charge can potentially serve as siRNA condensing agents as well as robust nano-vectors for targeted delivery. In addition, their surface functionality permits conjugation of drugs and genes or development of hybrid systems for combination therapy. Thus far, in vitro cellular testing of dendrimer-mediated siRNA delivery has revealed great potential, with reports on their in vivo effectiveness starting to appear. These favorable outcomes portend a promising future for dendrimer mediated RNAi therapeutics.